Healthcare service quality and inpatient satisfaction among participants of the National Health Insurance-Contribution Assistance Recipients (JKN-PBI) programme - Abdullah, Ardiani; Siregar, Santy Deasy; Hartono, Hartono (Buletin Kedokteran & Kesehatan Prima, 2025)
This research analyzes healthcare service quality and its impact on inpatient satisfaction among National Health Insurance-Contribution Assistance Recipient (JKN-PBI) participants at Muyang Kute Regional General Hospital, Bener Meriah Regency, Indonesia. Employing a descriptive-analytical survey design with a cross-sectional approach, data was collected from 69 randomly selected JKN-PBI inpatients using questionnaires. The study examined five service quality dimensions: tangibles, reliability, responsiveness, empathy, and assurance, and their relationship with patient satisfaction. Bivariate analysis using the Chi-square test revealed that reliability (p=0.003) and assurance (p=0.000) significantly influenced patient satisfaction, while tangibles, responsiveness, and empathy did not show statistically significant relationships (p>0.05). Reliability and assurance, reflecting consistent service delivery and staff competence, were crucial in fostering patient trust and satisfaction. Empathy, though not statistically significant, showed a trend towards positively influencing satisfaction, indicating a need for improvement in patient-centered care. The findings highlight the importance of reliability and assurance in enhancing JKN-PBI patient satisfaction. Recommendations include implementing training programs to improve staff empathy, maintaining high standards in reliability and assurance, and continuous patient feedback monitoring.